Hydrogen and oxygen stable isotope composition of water in metaschoepite mineralization on U3O8. (January 2020) - Oerter, Erik J.; Singleton, Michael; Dai, Zurong; Deinhart, Amanda; Thaw, Melissa; Davisson, M. Lee
Abstract: When exposed to humidity in an oxidizing atmosphere hydrated uranium oxide grows as a secondary mineral on aged U3 O8 and may incorporate the oxygen stable isotope signature of the water vapor into the secondary uranium oxide, as well as hydrogen and oxygen stable isotopes into any mineral hydration water. Because geospatial variation in δ 2 H and δ 18 O values of atmospheric humidity and precipitation is well understood, the H and O stable isotope composition of mineral hydration waters can give information on the environment of mineral formation. We exposed powdered U3 O8 to humidity with known H and O stable isotope composition at constant 30%, 61% and 91% relative humidity. We sampled and analyzed the U3 O8 powders along with any secondary hydrated minerals that had formed on the particle surfaces at various intervals from 1 to 10 days throughout the 180-day humidity exposures. We present stable H and O isotope results of mineral hydration waters in uranium oxide materials analyzed by thermogravimetry-enabled isotope ratio infrared spectroscopy (TGA-IRIS), which uses precise heating by thermogravimetric analyzer to liberate water vapor for subsequent online isotope analysis via a laser-based isotope ratio infrared spectroscopy instrument (Picarro L-2130i). Scanning electron microscopy (SEM), transmission electron microscopy (TEM), and x-ray diffraction (XRD) analysis of humidity-exposed U3 O8 heated to 350 °C indicates that the U3 O8 had a measurable metaschoepite ((UO3 )2H2 O) phase along with α-U3 O8 . After heating to 350 °C, the metaschoepite is eliminated but the α-U3 O8 is retained, meaning that the heating successfully extracted the water in the metaschoepite but did not disturb the crystalline structure of the U3 O8 . Analysis of the bulk oxygen isotope composition by fluorination of these samples before and after heating, indicates that the oxygen isotope value of the U3 O8 is also not affected by heating to 350 °C. Precision for δ 2 H and δ 18 O values of metaschoepite mineral hydration water stable isotope values yielded by the TGA-IRIS method on metaschoepite are 5.86‰ for δ 2 H, and 0.34‰ for δ 18 O. Hydrogen in the various water reservoirs is highly exchangeable and thus the δ 2 H values of these waters is not easily interpreted. However, oxygen in the separate water reservoirs is much less exchangeable, and thus δ 18 O values of the metaschoepite mineral hydration water is likely to reflect that of the water vapor the sample was exposed to. Once metaschoepite is formed on the surface of U3 O8 particles, the oxygen isotope signature of the mineral hydration water in metaschoepite does not respond to changes in exposure vapor isotopic composition, and thus appears to be fairly durable in this regard. These results suggest that it may be possible to discern information about the provenance and history of an oxidized U3 O8 sample from oxygen stable isotope measurements of metaschoepite mineral hydration water. Highlights: We exposed U3 O8 to air with constant humidity, and hydrogen and oxygen stable isotope composition. We measured the stable isotopes of hydration water in metaschoepite that formed on the U3 O8 . δ 18 O values of the metaschoepite hydration water are likely to reflect that of the water vapor the sample was exposed to. Oxygen isotopes of metaschoepite mineral hydration water may retain information on the location of mineral formation.